Energy footprints and the international trade network: A new dataset. Is the European Union doing it better? - Octavio Fernández-Amador; Joseph F. Francois; Doris Oberdabernig; Patrick Tomberger (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
Understanding the global energy network and the developments of energy efficiency is key to advance energy regulation and fight climate change. We develop a global panel dataset on energy usage inventories based on territorial production, final production and consumption over 1997-2014. We apply structural decomposition analysis to isolate energy efficiency changes and study the effectiveness of the European Union Energy Services Directive (2006/32/EC) on energy efficiency. High-income regions are net-importers of embodied energy and use a larger share of non-renewable energy than developing countries. The effectiveness of the Directive is mixed. The different ambition of national energy policies of the European Union members and some complementarity in supply chains underlie the different dynamics found. High-income countries share efficiency gains and changes in the mix of energy sources. These trends are not specific to the European Union. Energy policies in high-income countries are less effective for energy footprints. Our findings are indicative of energy leakage. Energy regulation should account for global supply chains and target energy footprints.
Keywords: F18; F64; O13; O44; Q40; Q54; Q56; 330; Energy usage; energy efficiency; energy footprints; renewable energy; MRIO analysis; Structural Decomposition Analysis; EU Energy Services Directive